STIGMA MASYARAKAT TERHADAP ORANG SAKIT JIWA - SYA'DIYAH, SITI NURUL; AFANDI, AGUS ARI; Pratama, Yoga Agus (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2015)
ABSTRACTThe stigma of society have an impact on the community with positive and negative consequences In fact a lot of mentally ill people in a community that is considered troubling. This study aims to determine how the public stigma against mentally ill people in the village Trucuk.The design of this study is descriptive survey approach a total population of 743 people and a sample of 100 non-probability sampling .Tehnik sampling is purposive sampling Taking appropriate degan researchers will use the inclusion criteria. The subjects in this study were the people in the village Trucuk, the number of 100 respondents, data collection using questionnaire instruments that describe the notion of mental illness.Results illustrate the largely negative public stigma by 59 people, while having a negative stigma by 41 people.The conclusion from the results of research conducted in May 2014 on "public stigma against mentally ill people in the Village District of Trucuk Trucuk Bojonegoro 2014" can be concluded in the Village District of Trucuk Trucuk Bojonegoro 2014, more than most have a negative stigma. It is hoped that the community will increase knowledge about mental illness, was able to provide assistance to the sick and mentally ill people understand not demonize and want to interact.    Keywords: Stigma, Community, mentally ill people